PRODUCTIVITY ANALYSIS OF FLOOR HERONING WORKERS USING WORK SAMPLING METHOD - Waldemar Waldemar; Nia Kartika; Siti Muawanah Robial (LPPM Universitas Negeri Jakarta, 2022)
Productivity is the ability to produce labor in completing the specified number of workers and determines the success of project implementation. Determination of minimum production through worker productivity analysis needs to be considered because it is correlated with the time of completion of work and affects the amount of project implementation costs required. The purpose of this study was to determine the productivity of iron workers in the construction project of the Aysha Islamic Hospital - Perum Accropolis Karadenan Cibinong Bogor. The method used for measuring productivity is work sampling with a productivity assessment approach of 12 (twelve) floor plate iron workers. The productivity value of iron workers varies every day, on the second day the lowest productivity is 28.85 Kg/Hour-Person and 33.55 Kg/Hour-Person on the thirteenth day being the highest productivity value. The average productivity obtained is 31.02 Kg/Hour-Person with a Labor Utilization Rate (LUR) of 74.27% over a span of 7 hours for 14 days. Keywords: Productivity, Work sampling, Reinforcing